2008
DOI: 10.1089/cpb.2007.0240
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Online Privacy among Teens: Risk Perception, Privacy Concerns, and Protection Behaviors

Abstract: Survey data from 395 high school students revealed that girls perceive more privacy risks and have a higher level of privacy concerns than boys. Regarding privacy protection behaviors, boys tended to read unsolicited e-mail and register for Web sites while directly sending complaints in response to unsolicited e-mail. This study found girls to provide inaccurate information as their privacy concerns increased. Boys, however, refrained from registering to Web sites as their concerns increased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
52
2
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(74 citation statements)
references
References 9 publications
6
52
2
6
Order By: Relevance
“…Perceived vulnerabilities to online risks are related to concern regarding privacy (Mohamed & Ahmed, 2012;Youn, 2009;Youn & Hall, 2008). Thus, the risk-benefit trade-off could potentially distinguish users from nonusers, and explain why users report less concern compared to non-users.…”
Section: Risk-benefit Trade-offmentioning
confidence: 99%
See 1 more Smart Citation
“…Perceived vulnerabilities to online risks are related to concern regarding privacy (Mohamed & Ahmed, 2012;Youn, 2009;Youn & Hall, 2008). Thus, the risk-benefit trade-off could potentially distinguish users from nonusers, and explain why users report less concern compared to non-users.…”
Section: Risk-benefit Trade-offmentioning
confidence: 99%
“…Thus, the risk-benefit trade-off could potentially distinguish users from nonusers, and explain why users report less concern compared to non-users. In other words, the users of SNSs are likely to be individuals who generally consider more benefits than risks likely to occur as a result of sharing information on SNSs, who in turn are expected to report less concern (Beldad et al, 2011;Mohamed & Ahmed, 2012;Youn, 2009;Youn & Hall, 2008). In this paper we will define the expectation of more benefits relative to risks as a positive risk-benefit trade-off.…”
Section: Risk-benefit Trade-offmentioning
confidence: 99%
“…Robust gender differences have been found regarding attitudes and behaviors related to online privacy [15][16][17][18][19]. When compared to males, females perceived greater privacy risks when online, reported higher levels of privacy concern, were more concerned about instituting laws aimed at protecting privacy online, were more likely to review and control available privacy settings online and were more likely to provide aliases on web-pages [18,19].…”
Section: Gender Differences In Privacy Attitudes and Behaviorsmentioning
confidence: 99%
“…When compared to males, females perceived greater privacy risks when online, reported higher levels of privacy concern, were more concerned about instituting laws aimed at protecting privacy online, were more likely to review and control available privacy settings online and were more likely to provide aliases on web-pages [18,19]. In addition, in a social networking setting, females engaged in various privacy protection behaviors more often than males, including greater discretion when posting and un-tagging photos, accepting friends and joining groups [20].…”
Section: Gender Differences In Privacy Attitudes and Behaviorsmentioning
confidence: 99%
“…In a number of studies, female internet users are found to be more concerned about their online privacy than their male counterparts (Cho, Rivera-Sanchez, & Lim, 2009;O'Neil, 2001;Sheehan, 1999;Youn & Hall, 2008); women also perceived more risks related to the disclosure of their personal data than men (Youn & Hall, 2008). As the level of risk perceptions increase, the tendency to seek information in an attempt to reduce these perceptions is also expected to intensify.…”
Section: Do Users' Demographics Matter?mentioning
confidence: 99%